The Role of Incubation Conditions on the Regulation of Muscle Development and Meat Quality in Poultry - Wang, Yuan-Hao; Lin, Jing; Wang, Jing; Wu, Shu-Geng; Qiu, Kai; Zhang, Hai-Jun; Qi, Guang-Hai (Frontiers in Physiology, 2022)
Muscle is the most abundant edible tissue in table poultry, which serves as an important source of high protein for humans. Poultry myofiber originates in the early embryogenic stage, and the overall muscle fiber number is almost determined before hatching. Muscle development in the embryonic stage is critical to the posthatch muscle growth and final meat yield and quality. Incubation conditions including temperature, humidity, oxygen density, ventilation and lighting may substantially affect the number, shape and structure of the muscle fiber, which may produce long-lasting effect on the postnatal muscle growth and meat quality. Suboptimal incubation conditions can induce the onset of myopathies. Early exposure to suitable hatching conditions may modify the muscle histomorphology posthatch and the final muscle mass of the birds by regulating embryonic hormone levels and benefit the muscle cell activity. The elucidation of the muscle development at the embryonic stage would facilitate the modulation of poultry muscle quantity and meat quality. This review starts from the physical and biochemical characteristics of poultry myofiber formation, and brings together recent advances of incubation conditions on satellite cell migration, fiber development and transformation, and subsequent muscle myopathies and other meat quality defects. The underlying molecular and cellular mechanisms for the induced muscle growth and meat quality traits are also discussed. The future studies on the effects of external incubation conditions on the regulation of muscle cell proliferation and meat quality are suggested. This review may broaden our knowledge on the regulation of incubation conditions on poultry muscle development, and provide more informative decisions for hatchery in the selection of hatching parameter for pursuit of more large muscle size and superior meat quality.